TOEFL Score Achievement as a Graduation Requirement in the Vocational Institute: Need Analysis on Maritime Institute - Laila Puspitasari Anggraini; Nur Patria Pujitama Sari (Yayasan Keluarga Guru Mandiri, 2023)
The Jakarta Maritime Institute is one of the vocational institutions that has a special requirement for their students to achieve a TOEFL score of 500 in all majors. The TOEFL test is considered normal as a graduation requirement, but in other cases, some students are concerned about the high TOEFL passing score determined by the institution. This study is conducted to analyze whether the TOEFL score with a passing score of 500 needs to be applied to prospective vocational graduates. The data were gathered through questionnaires and interviews from three categories of respondents: level IV students, alumni, and shipping company management as users of fresh graduates from this institution. The result of this study proved that most of the respondents stated the minimum TOEFL test score of 500 was unnecessary for graduation requirements. Therefore, this study concludes that the TOEFL score is considered very difficult for students to achieve. So, the institution, particularly vocational schools, should determine the TOEFL passing grade based on the school’s characteristics.